2003
DOI: 10.2355/isijinternational.43.489
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of TiAl Based Alloy in a Gaseous Hydrogen Atmosphere in a Temperature Range from Room Temperature to 973 K

Abstract: Ti-48Al-2Cr-2Nb (at%) with a g phase structure was tensile-tested in a high purity hydrogen gas in a temperature range of room temperature to 973 K. The reduction of elongation was observed in hydrogen gas in the entire temperature range, although the fracture surface changed mainly from cleavage to grain boundary facets both in vacuum and in hydrogen gas as the temperature increases. From transmission electron microscopy, fractography, the content of hydrogen introduced during tensile testing, and considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As shown in figure 4, the frequency of large particles increases and that of small particles decreases after 100 h ageing. After a stasis region where the number density does not change, coarsening occurs, where the mean particle radius tends to change in proportion to 1 3 . This is described as Ostwald ripening [28].…”
Section: Particle Sizementioning
confidence: 99%
See 1 more Smart Citation
“…As shown in figure 4, the frequency of large particles increases and that of small particles decreases after 100 h ageing. After a stasis region where the number density does not change, coarsening occurs, where the mean particle radius tends to change in proportion to 1 3 . This is described as Ostwald ripening [28].…”
Section: Particle Sizementioning
confidence: 99%
“…Niobium is an important solute in the design of heat-resistant stainless steels for automotive exhaust systems [1][2][3][4][5]. When in solid solution, it improves both the high temperature strength and the resistance to thermal fatigue [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of plastic deformation, the hydrogen ions generated by the catalytic Al element are transported to the crack tip by moving dislocations and diffusing along the pipes of the dislocation nucleus [ 34 , 35 , 36 ]. Meanwhile, dislocations, grain boundaries, phase interfaces and crack surfaces, which connect to the free surface, can provide fast diffusion paths for hydrogen absorbed from the material surface [ 37 , 38 ]. Therefore, the local accumulation of hydrogen is considered to cause the reduction of elongation, resulting in hydrogen–induced environmental embrittlement.…”
Section: Discussionmentioning
confidence: 99%
“…pct Al alloy with a dual-phase microstructure and the Ti-48Al-2Cr-2Nb alloy with a ␥-phase microstructure, it has been reported that the presence of hydrogen, whether it exists inside or outside the material, resulted in a reduction in the tensile elongation in the range of temperatures up to 573 K [20,21] or 973 K. [22] It has been suggested that the internal hydrogen embrittlement may be attributed to the reduced cohesive strength of the lattice; the external hydrogen embrittlement, on the other hand, may be attributed to the hydrogen-enhanced localized plastic deformation. [20,21,22] The temperature range in which the high-temperature environmental embrittlement occurs in this study is similarly extended to 1000 K. At the moment, the specific mechanism by which the present high-temperature environmental embrittlement could be understood has not yet been explained. Certainly, more detailed observations of hydrogen behavior and kinetics, in association with plastic deformation and the microstructure of TiAl-based alloys, are required.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] For the Ti-49 at. pct Al alloy with a dual-phase microstructure, it has been reported that the presence of hydrogen, whether inside or outside the material, resulted in a reduction in the tensile elongation at temperatures up to 573 K. [20,21] Also, a recent study showed that a Ti-48Al-2Cr-2Nb alloy with a ␥-phase structure showed a reduction in tensile elongation in hydrogen gas, within the range of temperatures from room temperature to 973 K. [22] On the other hand, some intermetallic alloys, such as boron-doped Ni 3 Al [23] and Ni 3 (Si,Ti) [24] alloys with an L1 2 structure deformed in air, have been reported to show reduced fracture stress and elongation at high temperatures. It has been suggested that oxygen atoms released from oxygen molecules (O 2 ) in air preferentially penetrate into the grain boundaries and then promote intergranular fracture, resulting in the so-called high-temperature environmental embrittlement.…”
Section: Introductionmentioning
confidence: 98%